1991
DOI: 10.1144/gsl.sp.1991.059.01.13
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting characteristics attributed to migration observed in petroleums reservoired in clastic and carbonate sequences in the Gulf of Mexico region

Abstract: Systematic differences among two subsets of petroleums selected geographically and by reservoir type were attributed to lithologically-characteristic migration phenomena. Most oils in offshore Louisiana Tertiary clastic reservoirs are deficient in light ends, evidently because of evaporative fractionation. Residual oils are enriched in cycloalkanes and aromatic hydrocarbons. Spuriously low evident maturities based upon concepts of paraffinicity are observed. Numerous oils are both fractionated and biodegraded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…LMW hydrocarbon parameters are useful tools for correlating oils, evaluating source maturity and types, and identifying secondary transformations in reservoirs, such as biodegradation, thermal alteration, water washing and evaporation (Thompson, 1983(Thompson, , 1987(Thompson, , 1988(Thompson, , 1995Schaefer and Littke, 1988;Halpern, 1995;ten Haven, 1996;Mango, 1997;Whiticar and Snowdon, 1999). However, n-alkanes, isoalkanes, cycloalkanes and monoaromatics in LMW hydrocarbons behave differently during TSR as discussed above, which is different from the pattern during kerogen maturation.…”
Section: Lmw Hydrocarbon Parametersmentioning
confidence: 99%
See 3 more Smart Citations
“…LMW hydrocarbon parameters are useful tools for correlating oils, evaluating source maturity and types, and identifying secondary transformations in reservoirs, such as biodegradation, thermal alteration, water washing and evaporation (Thompson, 1983(Thompson, , 1987(Thompson, , 1988(Thompson, , 1995Schaefer and Littke, 1988;Halpern, 1995;ten Haven, 1996;Mango, 1997;Whiticar and Snowdon, 1999). However, n-alkanes, isoalkanes, cycloalkanes and monoaromatics in LMW hydrocarbons behave differently during TSR as discussed above, which is different from the pattern during kerogen maturation.…”
Section: Lmw Hydrocarbon Parametersmentioning
confidence: 99%
“…The investigations of Thompson (1983Thompson ( , 1987Thompson ( , 1988Thompson ( , 1995 demonstrated that LMW hydrocarbons can be used to classify the types and thermal maturity of petroleum and evaluate secondary alteration in reservoirs, such as evaporative fractionation, water washing and biodegradation. Commonly used hydrocarbon parameters include heptane value, isoheptane value, n-heptane/methylcyclohexane and toluene/n-heptane (Thompson, 1988).…”
Section: Thompson Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…The composition of the residual oil can be interpreted according to both the fractionation depth and the gas volume required to fractionate the oil [15] . In fact, gas washing and evaporative fractionation have been used to describe phase fractionation caused by multiple stage geological events or mixed processes with oils and gases [16][17][18][19][20] .…”
Section: Secondary Alterations Of Kekeya Oils and Condensatesmentioning
confidence: 99%